Adherence to the Mediterranean diet is inversely related to binge eating disorder in patients seeking a weight loss program. Issue 1 (February 2015) - Bertoli, Simona; Spadafranca, Angela; Bes-Rastrollo, Maira; Martinez-Gonzalez, Miguel Angel; Ponissi, Veronica; Beggio, Valentina; Leone, Alessandro; Battezzati, Alberto
Summary Background & aim The key factors influencing the development of Binge Eating Disorder (BED) are not well known. Adherence to the Mediterranean diet (MD) has been suspected to reduce the risk of several mental illnesses such as depression and anxiety. There are no existing studies that have examined the relationships between BED and MD. Methods Cross-sectional study of 1472 participants (71.3% women; mean age: 44.8 ± 12.7) at high risk of BED. A MD score (MED-score) was derived from a validated food frequency questionnaire and BED by Binge Eating Scale questionnaire (BES). Body mass index, waist circumference and total body fat (%) were assessed by anthropometric measurements. Results 376 (25.5%) cases of self reported BED were identified. 11.1% of participants had a good adherence to MD (MED-score≥9). After adjustments for age, gender, nutritional status, education, and physical activity level, high MED-score was associated with lower odds for BED (odds ratios and 95% confidence intervals of a BED disorder for successive levels of MED-score were 1 (reference), 0.77 (0.44, 1.36), 0.66 (0.37, 1.15), 0.50 (0.26, 0.96), and 0.45 (0.22, 0.55) (P for trend: <0.01). Olive oil and nut consumption were associated with low risk of BED development whereas butter, cream, sweets and commercial bakery/sweets/cakes consumption increased the risk. We did not find a cumulative effect of depression and anxiety on MED-score in binge eaters. Conclusions These results demonstrate an inverse association between MD and the development of BED in a clinical setting among subjects at risk of BED. Therefore, we should be cautious about generalizing the results to the whole population, although reverse causality and confounding cannot be excluded as explanation. Further prospective studies are warranted.